2004
DOI: 10.1289/txg.7296
|View full text |Cite
|
Sign up to set email alerts
|

Renal Toxicogenomic Response to Chronic Uranyl Nitrate Insult in Mice

Abstract: Although the nephrotoxicity of uranium has been established through numerous animal studies, relatively little is known about the effects of long-term environmental uranium exposure. Using a combination of conventional biochemical studies and serial analysis of gene expression (SAGE), we examined the renal responses to uranyl nitrate (UN) chronic exposure. Renal uranium levels were significantly increased 4 months after ingestion of uranium in drinking water. Creatinine levels in serum were slightly but signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…Des travaux de toxico-génomique menés sur des souris exposées au nitrate d'uranyle soit par l'eau de boisson (80 mg/L) soit par injection intra-péritonéale (5 mg/kg) montrent des perturbations de l'expression génique de plus de 200 gènes dont certains impliqués dans le stress oxydant, la transduction des signaux cellulaires, le transport ou encore le métabolisme et le catabolisme cellulaire (Taulan et al, 2006(Taulan et al, , 2004. L'altération du métabolisme cellulaire est en effet un facteur important de la toxicité cellulaire de l'uranium (Banday et al, 2008b ;Brady et al, 1989 ;Fleck et al, 2002) et peut être mis en relation avec les conséquences histologiques et fonctionnelles décrites précédemment.…”
Section: Signalisation Cellulaireunclassified
“…Des travaux de toxico-génomique menés sur des souris exposées au nitrate d'uranyle soit par l'eau de boisson (80 mg/L) soit par injection intra-péritonéale (5 mg/kg) montrent des perturbations de l'expression génique de plus de 200 gènes dont certains impliqués dans le stress oxydant, la transduction des signaux cellulaires, le transport ou encore le métabolisme et le catabolisme cellulaire (Taulan et al, 2006(Taulan et al, , 2004. L'altération du métabolisme cellulaire est en effet un facteur important de la toxicité cellulaire de l'uranium (Banday et al, 2008b ;Brady et al, 1989 ;Fleck et al, 2002) et peut être mis en relation avec les conséquences histologiques et fonctionnelles décrites précédemment.…”
Section: Signalisation Cellulaireunclassified
“…In vivo studies, performed in rats and mice, demonstrated that DU alters gene expression, particularly of genes involved in apoptosis (Taulan et al 2004;Monleau et al 2006;Wan et al 2006). In human renal cells, the expression of genes related to apoptosis was also reported to be altered after exposure to DU (Prat et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…SAGE differs from microarrays in that it can be used to identify unknown gene sequences (for review see Tuteja and Tuteja 2004). There are only a limited number of studies that have used SAGE in toxicology applications (Hudkins et al 2001;Epperly et al 2002;Nonaka et al 2004;Taulan et al 2004). The utility and specificity of SAGE was corroborated in a study in which SAGE identified over 200 transcripts that changed following chronic exposure to uranyl nitrate in mice, while conventional endpoint analyses were unable to significantly distinguish treated vs. control animals, (Taulan et al 2004).…”
Section: Transcriptomicsmentioning
confidence: 99%